Labor market in the UK in digital era: The gender dimension - E. A. Mosakova; K. Kizilova (RUDN journal of Sociology, 2021)
The article considers gender discrimination in the field of labor relations in the United Kingdom (UK) in the pre-covid period. In the past decades, the Western European countries have made the most significant progress in achieving gender equality in various fields, including labor relations, and became the world leader in this area. However, despite all the efforts of the international community, no country has achieved a full gender equality, and Great Britain is no exception. The authors argue that the British anti-discrimination legislation (before leaving the European Union) was based on international acts and conventions. For a long time, there were acts and laws prohibiting discrimination in the labor market, which seriously hindered the implementation of an effective anti-discrimination policy in the sphere of labor relations. It was not until 2010 that the law on equality was passed to replace all previous laws and regulations and to provide an exhaustive list of criteria for prohibiting discrimination. As a result, Great Britain began to develop a rather strict national anti-discrimination legislation in the field of labor relations. Thus, in the past decades, the UK has been achieving gender equality in the economic sphere at a faster pace than the average European Union country. The study shows a steady decline in the gender wage gap in the UK over the past two decades, which may be considered one of the countrys most significant achievements in fighting gender discrimination in the labor market. However, there is still a number of serious challenges: a relatively low female labor force participation and employment rate, a gender wage gap and income gap, horizontal and vertical segregation, a gender gap in postgraduate education, and a significant gender gap in time spent on family responsibilities. Age discrimination presents a special problem in the sphere of labor relations in Great Britain. In the European Union, the first laws prohibiting age discrimination were adopted only in the 2000s, and in the UK - in 2006. This problem still remains extremely acute for the labor market, since age discrimination in the UK ranks third among the most common grounds for discrimination - after gender and disability.